Purchasing Power : The Economics of Modern Jewish History - Kobrin, Rebecca; Teller, A. (Book collections on Project MUSE., 2015)
Purchasing Power repositions economics in our understanding of the Jewish experience from early modern Rome to contemporary America and traces how economic circumstances have formed the context for, and even underpinned, Jewish intellectual, culture, and political development.